1996
DOI: 10.1016/0014-5793(96)00847-2
|View full text |Cite
|
Sign up to set email alerts
|

Delineating functionally important regions and residues in the cathepsin B propeptide for inhibitory activity

Abstract: Synthetic peptides derived from the proregion of rat cathepsin B were used to identify functionally important regions and residues for cathepsin B inhibition. Successive 5 amino acid deletions of a 56 amino acid propeptide from both the N-and Ctermini has allowed the identification of two regions important for inhibitory activity: the NTTWQ (residues 21p-25p) and CGTVL (42p--46p) regions. Alanine scanning of residues within these two regions indicates that Trp-24p and Cys-42p contribute strongly to inhibition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 20 publications
1
24
1
Order By: Relevance
“…Although proregion-derived peptides can specifically interact with their cognate enzyme, the K i values are too high to make these peptides efficient inhibitors. Nevertheless these values compare with those found for procathepsin-B-derived peptides (27,36). Crystallographic data have shown that this part of the proregion, which is flexible and fits into the active site of the catalytic domain, contributes weakly to the overall binding energy of interaction between the enzyme and the propeptide (25).…”
Section: Selective Inhibition Of Trypanosomal Versus Mammalian Enzymementioning
confidence: 76%
“…Although proregion-derived peptides can specifically interact with their cognate enzyme, the K i values are too high to make these peptides efficient inhibitors. Nevertheless these values compare with those found for procathepsin-B-derived peptides (27,36). Crystallographic data have shown that this part of the proregion, which is flexible and fits into the active site of the catalytic domain, contributes weakly to the overall binding energy of interaction between the enzyme and the propeptide (25).…”
Section: Selective Inhibition Of Trypanosomal Versus Mammalian Enzymementioning
confidence: 76%
“…The interactions within the S sites with concomitant hydrogen bonds to the highly conserved Gly68 are similar in the investigated structures. Although these interactions provide significant binding energy, 37 they do not differ greatly between the two enzymes. The anchoring role of proregion residues that occupy the S2-S3 sites is confirmed also by the structure of the wild type procathepsin L in which the Cys25 is oxidized.…”
Section: Discussionmentioning
confidence: 98%
“…The species distribution of CTLA-2-like proteins has not been explored. Inhibitory regions of the 56-aminoacid rat cathepsin B proregion have also been examined (Chen et al, 1996). Two regions were identified that caused 150-and 625-fold increases in the Ki.…”
Section: Figurementioning
confidence: 99%